Communication Needs of Patients with Breast Cancer: A Qualitative Study - Khoshnazar, Tahereh Alsadat Khoubbin (Indian J Palliat Care, 2016)
INTRODUCTION: Since communication is considered to be one of the central concepts in caregiving practices, this study aims to examine the perception of women with breast cancer in terms of their communication needs. METHODS: In this qualitative study, 20 participants (9 women with breast cancer, 10 of health-care professionals, and one family caregiver) were selected through purposive sampling, and a face-to-face semi-structured interview was conducted with each of them. After data collection, all interviews were transcribed and reviewed, and categories were extracted. The data were analyzed with Conventional Content Analysis of Landman and Graneheim using MAXQDA10 software. RESULTS: The analysis resulted in two extracted categories: “therapeutic communication” and “facilitating empathy”, and five subcategories: “trust-building therapist”, “crying out to be heard,” “seeking a soothing presence,” “sharing knowledge,” and “supportive peers”. CONCLUSION: Identifying and promoting the communicative needs of patients could lead to a considerably better care of patients under treatment. Therefore, therapeutic communication, as an integral part, should be incorporated into the care plan for patients with breast cancer and their families in the Oncology and Palliative Care wards.